2017
DOI: 10.3390/ijms18040811
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinesis Failure Leading to Chromosome Instability in v-Src-Induced Oncogenesis

Abstract: v-Src, an oncogene found in Rous sarcoma virus, is a constitutively active variant of c-Src. Activation of Src is observed frequently in colorectal and breast cancers, and is critical in tumor progression through multiple processes. However, in some experimental conditions, v-Src causes growth suppression and apoptosis. In this review, we highlight recent progress in our understanding of cytokinesis failure and the attenuation of the tetraploidy checkpoint in v-Src-expressing cells. v-Src induces cell cycle ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 93 publications
0
22
0
Order By: Relevance
“…Although Src, to our knowledge, has not been directly implicated with maintaining mitotic fidelity, it has been shown to promote MT nucleation and regrowth (Colello et al, 2010) by binding to γ-tubulin complexes (Kukharskyy et al, 2004). In addition, Src was found to facilitate spindle orientation (Nakayama et al, 2012), and oncogenic v-Src has been associated with cytokinesis failure (Nakayama et al, 2017). This study revealed that Src inhibition results in increased MT polymerization rates, thus exacerbating the CIN phenotype imposed by Mad2 loss.…”
Section: Synthetic Lethal Interaction Between Inhibition Of the Sac Amentioning
confidence: 99%
“…Although Src, to our knowledge, has not been directly implicated with maintaining mitotic fidelity, it has been shown to promote MT nucleation and regrowth (Colello et al, 2010) by binding to γ-tubulin complexes (Kukharskyy et al, 2004). In addition, Src was found to facilitate spindle orientation (Nakayama et al, 2012), and oncogenic v-Src has been associated with cytokinesis failure (Nakayama et al, 2017). This study revealed that Src inhibition results in increased MT polymerization rates, thus exacerbating the CIN phenotype imposed by Mad2 loss.…”
Section: Synthetic Lethal Interaction Between Inhibition Of the Sac Amentioning
confidence: 99%
“…v-Src regulates proliferation and cell survival through modification of growth regulatory signal transduction and affects migration by acting on actin cytoskeleton remodeling (2,5). In addition to these oncogenic effects, suppression of cell proliferation has been observed under some experimental conditions (2,(5)(6)(7). In one experiment (6), we used three cell lines, HeLa S3, HCT116, and NIH3T3, capable of inducing doxycycline (Dox) 2 concentration-dependent expression of v-Src.…”
mentioning
confidence: 99%
“…Furthermore, v-Src induces chromosome bridge formation through the caffeine-sensitive DNA damage response (25). This can lead to further cytokinesis failure by attenuating the abscission checkpoint through Aurora B delocalization from the spindle midbody (7). Therefore, v-Src-induced disturbance of cell division can generate genetic diversity, and this pathway may be involved in the oncogenic effect of v-Src.…”
mentioning
confidence: 99%
“…Although, to our knowledge, Src has not been directly implicated with maintaining mitotic fidelity, Src has been shown to promote microtubule nucleation and regrowth (Colello et al , 2010) by binding to gamma-tubulin complexes (Kukharskyy et al , 2004). Additionally, Src was found to facilitate spindle orientation (Nakayama et al , 2012), and oncogenic v-Src has been associated with cytokinesis failure (Nakayama et al , 2017). This study revealed that Src inhibition results in increased MT polymerization rates, thus exacerbating the CIN phenotype imposed by Mad2 loss.…”
Section: Discussionmentioning
confidence: 99%